ON THE FEATURES OF CONSUMER CHOICE IN THE CONTEXT OF MICROECONOMIC SCIENCE - Г. П. Жалдак; А. Р. Дунська; С. С. Ринденко (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2024)
The purpose of the research of this article is to consider the features of consumer choice in the context of microeconomics. The first manifestations of the theories of utility and consumer choice among representatives of the Austrian school and their further evolution are considered. Considerable attention is paid to consideration of various paradoxes that took place in the process of economic crises and mostly related to manifestations of irrational behavior of consumers. A survey of students was conducted on the basis of which their consumer basket was formed. a comparison of their choice with the choice of people of an older age category was made. In the process of writing the article, general scientific methods of scientific knowledge, induction, deduction, analysis, synthesis and systematization were used; as well as methods of observation and questionnaires; graphic method - to present the results of the study. The results of the study provided an opportunity to form a consumer basket of students and to determine the peculiarities of its formation in the conditions of martial law. The practical significance of the research results lies in the fact that the results of the survey can to some extent be used by enterprises in the formation of their price and marketing strategies.